Investigation of the interaction of an automobile wheel with a vertical obstacle - Sokolovskij, Edgar (Transport, 2005)
Collision of automobile wheels with a vertical obstacle as a result of which the wheel tire gets dismantled is considered in the present article. The required force and the minimal speed of driving which is equivalent to the expenditures of the kinetic energy necessary for dismantling of the tire from the wheel rim after the collision with an obstacle are ascertained. The values of this force and speed typical of automobiles attributed to different classes, their dependence upon the height of the obstacle and the angle of collision with the obstacle are fixed. A more precise method for the calculation of the automobile speed prior to the traffic accident taking into consideration the expenditures of the kinetic energy necessary for dismantling of the wheel after the occurrence of its collision with a vertical obstacle is suggested.First Published Online: 27 Oct 2010